Training and Assistance for Village-Owned Enterprises (Bumdes) Based on Local Potential in Babalanlor Village, Bojong District, Pekalongan Regency - Tarmidzi Tarmidzi; M. Aries Syafi'i; M. Yusron (Islamic Studies Journal for Social Transformation, 2018)
BUMDes is a village-owned enterprises formed by the community to achieve independence and prosperity of the village. The purpose of BUMDes is as an instrument of social capital which is expected to be a prime over in bridging efforts to strengthen the rural economy. In order to create an independent and prosperous village, we require the involvement of other parties, including the involvement of the community, groups, practitioners, academics and government. IAIN Pekalongan, as one of the tertiary institutions which have done community services and has concern in the community welfare problem.Through an action research method completed with data collection techniques through participatory observation, interviews, documentation, and focus group discussions, an action plan is developed. The community service team of State Islamic Institute of Pekalongan together with the community has provided assistance in the process of making BUMDes based on local potential. Through the assistance program for making BUMDes in Babalanlor Village, the village has produced the outputs and the outcomes. First, BUMDes named Sukses Mulyo along with its statutes/bylaws. Second, the assisted community already has an awareness of the importance of BUMDes because with their presence, BUMDes is expected to be able to play a role in increasing Village’s Original Income (PADes) resources, providing services to the needs of the community, increasing business opportunities and reducing unemployment in rural areas, increasing rural income, and reducing poverty.